2011
DOI: 10.1111/j.1095-8312.2011.01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular evidence indicates that the Gulf Coast box turtle (Terrapene carolina major) is not a distinct evolutionary lineage in the Florida Panhandle

Abstract: Four extant subspecies of Terrapene carolina in eastern North America, Terrapene carolina bauri, Terrapene carolina carolina, Terrapene carolina triunguis, and Terrapene carolina major, are recognized based on morphological studies. A fifth subspecies, Terrapene carolina putnami, has been described from Pleistocene deposits but is very similar morphologically to T. c. major. Questions concerning the relationship of the Gulf Coast box turtle (T. c. major) to other box turtles have been pervasive ever since it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 44 publications
3
52
1
Order By: Relevance
“…2006; Lemmon et al. 2007; Beamer & Lamb 2008; Jackson & Austin 2010; Butler et al. 2011), other studies of southeastern taxa show phylogenetic breaks that are not specific to the suture zone (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2006; Lemmon et al. 2007; Beamer & Lamb 2008; Jackson & Austin 2010; Butler et al. 2011), other studies of southeastern taxa show phylogenetic breaks that are not specific to the suture zone (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Although this pattern is common among some North American taxa (e.g. Austin et al 2002;Masta et al 2002;Church et al 2003;Lemmon et al 2007;Beamer & Lamb 2008;Jackson & Austin 2010;Butler et al 2011), other studies of southeastern taxa show phylogenetic breaks that are not specific to the suture zone (e.g. Avise et al 1979Avise et al , 1987Donovan et al 2000;Zamudio & Savage 2003;Gamble et al 2008;Degner et al 2010;Makowsky et al 2010).…”
Section: Patterns Of Genetic Structure In the Southern Leopard Frogmentioning
confidence: 97%
“…However, for the rapidly evolving D-loop Butler et al (2011) found T. carolina not to be paraphyletic with respect to T. coahuila. Yet, they reported nearly identical haplotypes of a T. carolina from Escambia County (Florida) and T. coahuila, but these haplotypes were highly distinct from all other haplotypes of T. carolina.…”
mentioning
confidence: 79%
“…However, if 14% are hybrids, 86% of the concerned populations must be pure, and this is evidence for the maintenance of largely distinct gene pools in sympatry. By contrast, T. carolina forms panmictic populations whenever different subspecies meet (Butler et al 2011), and this is fundamentally different from the situation in T. carolina and T. ornata. Consequently, the recognition of T. mexicana as a species distinct from T. carolina, as proposed by Martin et al (2013Martin et al ( , 2014, is unwarranted.…”
mentioning
confidence: 84%
See 1 more Smart Citation